Tooth Loss and Metabolic Syndrome in South Korea: The 2012 Korean National Health and Nutrition Examination Survey. Issue 16 (April 2016) - Kim, Si-Wan; Cho, Kyung-Hwan; Han, Kyung-Do; Roh, Yong-Kyun; Song, In-Seok; Kim, Yang-Hyun
Abstract : Abstract: To evaluate the relationship between tooth loss and metabolic syndrome (MS) in South Korean adults. Subjects and Methods: A total of 3589 adults (1511 men and 2078 women aged over 40 years) from the 2012 Korean National Health and Nutrition Examination Survey were included and divided into 3 groups according to the number of remaining teeth (0–19, 20–27, and 28). We recorded the number of remaining teeth and measured MS components such as waist circumference, systolic and diastolic blood pressure, fasting blood glucose, serum high-density lipoprotein-cholesterol, and triglyceride concentration. We also calculated the number of subjects who met the inclusion criteria of MS in each group. Multiple logistic regression analysis was performed to estimate the prevalence of MS components according to the number of remaining teeth after adjusting for covariates. Women without MS had significantly more teeth than those with MS (24.5 ± 0.2 vs 21.0 ± 0.3). In men, the prevalence of high blood pressure and high fasting blood glucose levels were significantly different among the 3 groups ( P  = 0.003 and P  < 0.001, respectively); however, the prevalence of MS and all MS components were significantly different in women ( P  < 0.001 for all comparisons). Men with 0 to 19 remaining teeth were most likely to have high blood pressure and high fasting blood glucose, while women with 0 to 19 remaining teeth had the highest prevalence of MS and each MS component. Multiple logistic regression analysis revealed that women with fewer remaining teeth had a higher prevalence of MS and MS components after adjusting for covariates. Having only a few remaining teeth was associated with MS in women in South Korea.